If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 5y + -2x Reorder the terms: 2x = -2x + 5y Solving 2x = -2x + 5y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2x + 2x = -2x + 2x + 5y Combine like terms: 2x + 2x = 4x 4x = -2x + 2x + 5y Combine like terms: -2x + 2x = 0 4x = 0 + 5y 4x = 5y Divide each side by '4'. x = 1.25y Simplifying x = 1.25y
| .3x-.5y=.6 | | 4tanx+2=-2 | | (2z-3)^2/5=(3z)^1/5 | | 14(v+20)=742 | | 0.3xn=0.24whatmyisn | | 2cosx-1+3secx=0 | | 8x+36=-4 | | 35a^2b^2/7a^1b^6 | | 5b-1+2b=6 | | 16.4d-12.95=19d+4.21 | | 9*x=24 | | -15.52-5.65+.1c=4.7c+19.31 | | 3x^2-30x+30=0 | | 4(2c-6)=7c | | 2n+2n=6 | | 14.3u=15.8u+9.6 | | 648-153x+9x^2=0 | | (-5)2+5= | | 14.73-8.6g+8.79=-12.1g-13.93 | | (-C)2+C= | | -3(2z-5y)-z= | | (2y-3)^2/3=(3y)^1/3 | | -14.6v+14.11=-18.5v-14.36 | | 0.3-0.07=x | | (2y-3)^2/3=(3y)^1^3 | | 6h+4h+12=34 | | -20+6b+15b=17b+16 | | -20-11h=-8h+19 | | 10q-55=-5+10q | | 1/9x^2=25 | | 5-f=-11+10f-17 | | 3/4x-12=4-9/4x |